2015
DOI: 10.1016/j.tjog.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation enhances peripheral serotonin secretion to regulate the large follicle steroidogenesis of rats

Abstract: These findings suggest that decreased serum estradiol concentrations in SD rats may be the result of serotonin-related inhibition of estradiol production and decreased large follicle expression of StAR protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…On one hand, it may be due to the inhibition of the hypothalamic-pituitary-adrenal (HPG) axis caused by elevated corticosteroids under certain stress conditions [24]. On the other hand, it was suggested that sleep deprivation could activate the serotonergic nervous system and promote the release of serotonin, therefore, serotonin suppressed FSH-induced estradiol release in large follicles [39]. Because serotonin inhibits estradiol production and decreases the expression of STAR protein in large follicles, estradiol concentrations may decrease during sleep deprivation [39].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, it may be due to the inhibition of the hypothalamic-pituitary-adrenal (HPG) axis caused by elevated corticosteroids under certain stress conditions [24]. On the other hand, it was suggested that sleep deprivation could activate the serotonergic nervous system and promote the release of serotonin, therefore, serotonin suppressed FSH-induced estradiol release in large follicles [39]. Because serotonin inhibits estradiol production and decreases the expression of STAR protein in large follicles, estradiol concentrations may decrease during sleep deprivation [39].…”
Section: Discussionmentioning
confidence: 99%
“…When ketanserin, an inhibitor of 5‐HT 2 receptors, is present in culture medium for the follicles, production of progesterone and testosterone decreases, and this effect is reversed by addition of pregnenolone (Tanaka et al., 1993 ). In contrast, addition of 5‐HT to the medium modifies expression of the protein that mobilizes cholesterol to the mitochondria, the steroidogenic acute regulatory protein (StAR), and the production of estradiol (Yang et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Partial similarity with this study’s results about the association of elevated T with serum serotonin in the SD group was observed in animal models. Although elevated serum serotonin levels were noted in sleep deprivation–induced rats ( Yang, Wu, Wu, Lin, & Tsai, 2015 ), luteinizing hormone (LH) secretion was inhibited. Lopez-Rodriguez, Wilson, Maidment, Poland, and Engel Jr. (2003) reported that sleep deprivation increased extracellular serotonin in the rat hippocampus.…”
Section: Discussionmentioning
confidence: 99%